The Effect of a Region's Location on It's Development - Vassilis Angelis; Eleni Gaki (European Regional Science Association (ERSA), 2006)
The sustainable development of a region depends on its power to attract industrial units. Industrial mobility, however, is largely a voluntary process. Hence, a region's growth or decline depends on its power to "pull" and "retain" industries but also the right blend of people to run them; this pulling power depends on what we call the Image of a region. At each time instant the region "sends out" its Image and depending on its impact on the people (both employers and employees) the region may be considered Attractive or Repulsive. The image of a region may be defined as a function of a multitude of factors physical, economic, social and environmental. One of those factors, ïn which our emphasis is placed in the present work, is the region's proximity to influence centers (markets, resources and decision centers). This proximity may be expressed through a variable, which is referred to as the region's Location Multiplier. As a first attempt to quantify this multiplier we may express it as a function of the region's distance and / or transportation cost to and from the main influence centers. Such an approach, although sound and realistic in most cases, has a serious shortcoming as it cannot take into account the problems of spatial discontinuity faced by remote and especially island regions. To overcome this problem we may extend the above function so as to include the region's spatial continuity dimension expressed by the availability in the region of all or only a number of the classic transportation modes. This new multiplier is clearly much improved as compared to the previous one, but still has a weakness, as it cannot take into account the opportunities offered to a remote region by the new Information and Communication Technologies. To alleviate this weakness we may extend the multiplier so as to include the information continuity dimension expressed by the availability in the region of the infrastructure required for the implementation of such technologies. Our objective in this paper is to define a region's Location Multiplier, going through the three stages described above, suggest ways of quantifying it and finally applying it to a number of regions in Greece, a country with many islands and thus having an intense spatial continuity problem but also a lot to gain from an information continuity situation.
Keywords: 330